Role of Vitamin K in CKD: Is Its Supplementation Advisable in CKD Patients? - Patrycja Grzejszczak; Ilona Kurnatowska (Karger Publishers, 2021)
Background: Patients with CKD are at an increased risk of developing vascular calcification (VC) and bone complications which translate into a higher morbidity and mortality. The dephosphorylated and uncarboxylated matrix Gla protein (dp-ucMGP) is considered to be an indicator of vitamin K2 status and correlates with markers of VC. It is activated by γ-glutamyl carboxylase that converts inactive MGP into an active form, and vitamin K2 is a cofactor of this reaction. The active form of MGP is a known inhibitor of arterial wall calcification and plays an important role in bone turnover. Recent studies show poor vitamin K2 status in CKD patients. We aimed to review the literature for the association between vitamin K2 status and calcification and bone disease risk and the efficacy of vitamin K2 supplementation in CKD population. Summary: Most CKD patients, including those on renal replacement therapy, have vitamin K2 deficiency. The dp-ucMGP level, a marker of vitamin K2 status, is decreased by vitamin K2 supplementation in CKD patients, but there is no unequivocal proof that it influences arterial calcification progression and bone complications. Key Messages: CKD population are at risk of vitamin K deficiency. Supplementation of vitamin K2 is safe and improves the serum markers of its deficiency. There is lack of strong evidence that vitamin K2 supplementation slows progression of calcification or reduces the frequency of bone complications. More prospective studies are needed.